Current knowledge and future research directions for the monitoring and management of visitors in recreational and protected areas. (March 2018) - Pickering, Catherine; Rossi, Sebastian Dario; Hernando, Ana; Barros, Agustina
Abstract: Visitation to recreation and protected areas is increasing globally and in many regions, including Europe, so is research on visitation. But who, where, what and how is the research done and what are the trends and key research gaps? The systematic quantitative review of 758 oral abstracts from the first seven conferences on Monitoring and Management of Visitors in Recreation and Protected Areas answers research questions on methods, goals and locations presented in the last decade as well as discussing trends and recommendations for the future. These major multi-disciplinary conferences are held every two years in different countries in Europe. Most (72%) of the research was from Europe, predominantly from countries where English is not the dominant language. Nearly every abstract was from terrestrial natural areas, often terrestrial protected areas (56%), with only three marine studies. Most abstracts (85%) were in the social sciences, either assessing visitor profile data along with motivations, satisfaction and experiences or focused on psychological aspects such as the attitudes, perceptions and behavior of visitors. Environmental research (32% abstracts) was mostly on vegetation, wildlife and landscape features with limited research on aquatic systems. Technology is driving research, with the analysis of big data from social media transforming where and how visitors can be monitored. Important gaps remain including research from countries and regions with large protected area systems and high levels of visitation including in Asia, South America and Africa, as well as some countries in Europe such as France. Management implications: The article describes the previous trends in this conference series on outdoor recreation. The findings suggest that future conferences could: ● enhance the attendance and representation of researchers from parts of Europe so far under represented and different parts of the world such as Asia, the Russian Federation and Africa to make the conference truly international, ● strengthen the relevance of the conference for practitioners and managers, and ● communicate the value of research, including how new methods and technologies can enhance sustainable decision making.